2011
DOI: 10.1007/s10803-011-1189-x
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Openness Toward Autism Spectrum Disorders: Improving Peer Acceptance

Abstract: One probable consequence of rising rates of autism spectrum disorder diagnosis in individuals without co-occurring intellectual disability is that more young adults with diagnoses or traits of ASD will attend college and require appropriate supports. This study sought to explore college students' openness to peers who demonstrate ASD-characteristic behaviors. Results showed a significant difference in openness between students who had a first-degree relative with an ASD (n = 18) and a gender-matched comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 29 publications
12
161
5
1
Order By: Relevance
“…The noted preference for living alone during college supports Neville and White's study indicating college students with autism desire solitary spaces [21]. One practical implication arises from this; colleges could offer students with autism their own dorm room and accommodate this need for their own space.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The noted preference for living alone during college supports Neville and White's study indicating college students with autism desire solitary spaces [21]. One practical implication arises from this; colleges could offer students with autism their own dorm room and accommodate this need for their own space.…”
Section: Discussionsupporting
confidence: 52%
“…Openness to college students with ASD varied by academic major. Engineering majors had the highest comfort level with students with ASD, physical science majors had the highest willingness to spend time with college students with autism, and social science majors scored highest in willingness to live near a student with autism [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the first peer-reviewed study to assess conceptions of autism among college students in the US, 685 students read a vignette describing a college student with characteristics (but not the label) of mild autism and then completed a self-report measure of openness towards the individual in the vignette (Nevill and White 2011). Students with a firstdegree relative on the spectrum reported more openness than their counterparts, with no overall gender differences in openness.…”
Section: Conceptions Of Asd In the Usmentioning
confidence: 99%
“…are beneficial to students with AD (Kohler & Field;2003;Nevill & White, 2011). Eaves and Ho (2008) reported that when families recalled what was helpful, it was the people even more than programs that were important to the success of the student.…”
Section: Qualitative Resultsmentioning
confidence: 99%